Structural and electrophysiological determinants of atrial cardiomyopathy identify remodeling discrepancies between paroxysmal and persistent atrial fibrillation - Huang, Taiyuan; Nairn, Deborah; Chen, Juan; Mueller-Edenborn, Bjoern; Pilia, Nicolas; Mayer, Louisa; Eichenlaub, Martin; Moreno-Weidmann, Zoraida; Allgeier, Juergen; Trenk, Dietmar; Ahlgrim, Christoph; Westermann, Dirk; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Progressive atrial fibrotic remodeling has been reported to be associated with atrial cardiomyopathy and the transition from paroxysmal to persistent atrial fibrillation(AF). We sought to identify the anatomical and electrophysiological factors involved in atrial remodeling that promote AF persistency. Methods: Consecutive patients with paroxysmal(n=134) or persistent(n=136) AF who presented for their first AF ablation procedure were included. Patients underwent high-definition mapping (1835 ± 421 sites/map) during sinus rhythm and were randomized to training and validation sets for model development and evaluation. A total of 62 parameters from both electro-anatomical left atrial(LA) mapping and non-invasive baseline data were extracted encompassing four main categories: (1)LA size, (2)extent of low-voltage-substrate(LVS), (3)LA voltages and (4)bi-atrial conduction time as identified by the duration of amplified P-wave(APWD) in a digital 12-lead-ECG. Least absolute shrinkage and selection operator(LASSO) and logistic regression were performed to identify the factors that are most relevant to AF persistency in each category alone and all categories combined. The performance of the developed models for diagnosis of AF persistency was validated regarding discrimination, calibration and clinical usefulness. Results: In training and validation sets, APWD (threshold 151ms), LA volume (threshold 94ml), bipolar LVS area <1.0 mV (threshold 4.55cm2) and LA global mean voltage (GMV, threshold 1.66mV) were identified as best determinants for AF persistency in the respective category. Moreover, APWD (AUC 0.851 and 0.801) and LA volume (AUC 0.788 and 0.741) achieved better discrimination than LVS extent (AUC 0.783 and 0.682) and GMV (AUC 0.751 and 0.707). The integrated model (combining APWD and LAV, which were identified after selection among all 62 parameters) yielded the best discrimination performance between AF types (AUC 0.876 in training set and 0.830 in validation set). The calibration performance and clinical usefulness were also superior in APWD and LAV. Conclusion: Among 62 electro-anatomical parameters, we identified APWD, LA volume, LVS extent and mean LA voltage as the four determinant electrophysiological and anatomical factors that are most indicative for AF persistency. Notably, the combination of APWD with LA volume enabled discrimination between paroxysmal and persistent AF with high accuracy, emphasizing their importance as underlying substrate of persistent AF.